Intertemporal Hedging and Trade in Repeated Games with Recursive Utility - Asen Kochov; Yangwei Song (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
Recursive preferences have found widespread application in representative-agent asset-pricing models and general equilibrium. A majority of these applications exploit two decision-theoretic properties not shared by the standard model of intertemporal choice: (i) agents care about the intertemporal distribution of risk and (ii) rates of time preference, rather than being exogenously fixed, may vary with the level of consumption. We investigate what these features imply in the context of a repeated strategic interaction. Specifically, we identify novel opportunities for the players to manage risk and trade intertemporally, and characterize when such opportunities lead to an expansion of the feasible set of payoffs. Sharp implications for equilibrium behavior and the folk theorem are also deduced.
Keywords: 330; recursive utility; repeated games; correlation aversion; endogenous discounting; intertemporal trade; intertemporal hedging